الإستثمار الخاص في المنشآت الرياضية عن طريق المؤسسات الصغيرة و المتوسطة - شلوش, بوعلام; دشيشة, عبد الرحمان (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى إبراز أهمية المؤسسات الصغيرة و المتوسطة ودورها كوسيلة للإستثمار الخاص في المنشآت الرياضية، اعتمدنا على المنهج التحليلي،حيث توصلنا في دراستنا إلى أن هناك معوقات ومشاكل تعيق من استمراريتها، واكبر مشكل هو التمويل إذ أن صغر حجم هذه المؤسسات يجعل حصولها على القروض المصرفية أمر صعب، فضلا عن المشاكل السياسية الاقتصادية والتوجهات الحكومية الإدارية . This study aimed to highlight the importance of small and medium enterprises and their role as a means of private investment in sports facilities, , we relied on the analytical approach, where we found in our study that there are obstacles and problems that hinder its continuity, and the biggest problem is financing, as the small size of these institutions makes it difficult to obtain bank loans, in addition to the political, economic problems and government administrative orientations.
Investment in sports Facilities through Small and Medium Enterprises
مقال
Keywords: الإستثمار ; ،التحديات ; المؤسسات الصغيرة والمتوسطة ; المنشآت الرياضية